Perilaku Keluarga Terhadap Tindakan Pencegahan Demam Berdarah Dengue Berdasarkan Health Belief Model: Family Behavior towards Dengue Fever Prevention Measures Based on the Health Belief Model Health Belief Model - Mery Lingga Anggraini; Jamal Sidiq (NERS Jurnal Keperawatan, 2017)
Dengue Haemorrhagic Fever is a disease such as disorders of the capillaries and the human blood clotting system caused by a viral infection. Until now, dengue fever is still a public health problem and a social and economic impacts. In the past year, the incidence of DHF work area Puskesmas Tanjung Paku In 2015 as many as 96 people. The purpose of this study is to describe the behavior of the family against Dengue preventive measures in RW 1 Kampung Jawa district of Tanjung Harapan Solok year 2016. The descriptive study was conducted in RW 1 Solok Kampung Jawa on June 1 to 14, 2016. the population in this study across the heads of family residing in Kampung Jawa RW 1 with a sampling technique total sampling at 55 people. Data were collected using a questionnaire with interviews and observations were then processed and analyzed. The results of the study, obtained the majority (69.1%) of respondents have the perception of vulnerability Good, Mostly (70.9%) of respondents perceive the severity Well, more than a majority (50.1%) of respondents perceive the benefits of Less Good, Mostly (72.7%) respondents perceive barriers good, Mostly (89.1%) of respondents do less well in Dengue prevention measures. Based on the results of the study are expected to be health workers in PHC Tanjung Paku specifically address the issue of dengue disease in order to educate especially the Head of the Family on the prevention of dengue in the home environment.